(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
Bronchial asthma is a disorder characterized by increased response of trachea and bronchioles to various stimuli resulting in wide spread narrowing of airways. It is an inflammatory disease of respiratory organs combined with inflammatory cell infiltration, epithelial damage and sub-epithelial fibrosis as its internal pathological picture. Its symptoms closely resemble with symptoms of Tamak Shwasa in Ayurveda. The present study was conducted on 81 patients at I.P.D. and O.P.D. level. Patients were given Albizia lebbeck stem bark decoction (Shireesh Twak Kwatha) in a dose of 50 ml thrice daily for 6 weeks, supported by light diet. The results were assessed in terms of clinical recovery, symptomatic relief and pulmonary function improvement. The effect of the treatment was assessed based on subjective and objective parameters. A significant increase in PEFR and considerable decrease in total leukocyte count, eosinophil count and E.S.R. were observed. From the study conducted, it was found that 56 % (28) cases has shown good response, 38 % (19) cases shown fair response, 6 % (03) cases shown poor response and 31 cases were dropouts. The results demonstrate that the formulation can be used as an effective drug in Bronchial asthma however detailed observational studies are required to demonstrate the effect of drug at molecular level.